Rituximab retreatment guided by CD27+ B-cell count vs. clinical relapse in anti-MAG polyneuropathy: a cost-effective approach with lower cumulative doses - Bellucci, Margherita; Capodivento, Giovanna; Massa, Federico; Bozzano, Federica; Bavestrello, Giacomo; Baroncelli, Elena; Cabona, Corrado; Cagnetta, Antonia; Schenone, Angelo; Nobbio, Lucilla; Benedetti, Luana (Frontiers in Neurology, 2025)
IntroductionRituximab (RTX) is a widely used treatment for anti-MAG polyneuropathy, though standardized maintenance strategies are lacking. We aimed to compare two RTX retreatment protocols: (1) a full course (375 mg/m2/week for 4 weeks) administered at clinical relapse, and (2) a single infusion (375 mg/m2) at reappearance of peripheral CD27+ B cells—to evaluate their impact on disability progression over time.Patients and methodsWe retrospectively enrolled 29 patients with anti-MAG polyneuropathy, dividing them into two cohorts: (1) relapse (n = 19), treated with a full course at clinical relapse, or (2) Kim's protocol (n = 10), treated based on peripheral CD27+ B cell monitoring. Changes in INCAT, MRC sum score, and ISS from baseline to last follow-up were assessed.Results and discussionNo significant changes in MRC scores were observed in either cohort. Both cohorts showed a significant reduction in INCAT scores at last follow-up, with a tendency toward greater improvement in Kim's protocol cohort. ISS scores were significantly lower in Kim's protocol cohort compared to the relapse cohort (p < 0.01). Importantly, patients treated according to Kim's protocol received a cumulative RTX dose ~2.5 times lower than those treated upon relapse (p < 0.0001), despite showing comparable or better clinical outcomes.ConclusionA tailored maintenance strategy guided by peripheral CD27+ memory B-cell monitoring enables reduced cumulative RTX exposure while preserving clinical efficacy. This approach may improve cost-effectiveness and reduce treatment burden in patients with anti-MAG polyneuropathy.